Magnesium ribbon and anaerobic granular sludge for conversion of CO2 to CH4 or biogas upgrading - Andronikou, Maria; Adamou, Vasiliki; Koutsokeras, Loukas E.; Constantinides, Georgios; Vyrides, Ioannis (My University, 2022)
There is a growing interest in biogas upgrading processes based on the use of hydrogenotrophic methanogens. Hydrogenotrophic methanogens utilize H2 and CO2 in converting them into CH4. In this work, a new approach for CO2 conversion to CH4 and biogas upgrading has been developed based on magnesium ribbon and anaerobic granular sludge under mild aqueous conditions; with CO2 as the sole carbon source, Mg(0) oxidizes and generates H2 that is utilized by hydrogenotrophic methanogens in anaerobic granular sludge. The Mg concentration (2 g/L) contributed to high H2 production during the first day; subsequently H2 gradually decreased/utilised with a simultaneous CH4 increase (days 1–4). Results show that 2 g/L Mg(0) in anaerobic granular sludge can generate 60 % CH4 after 7 days. In this system, the daily regulation of pH to 6 can increase the CH4 to 71.4 % after 7 days, while biogas can be converted to 92 % CH4 after 9 days. At these conditions, Nesquehonite (MgCO3·3H2O) is formed at the outer surface of Mg(0) which prevents the H2 released from Mg(0). However, Nesquehonite (MgCO3·3H2O) can be potentially used as construction materials. Therefore, a new process is reported to convert CO2 to CH4 and Nesquehonite based on Mg(0) and anaerobic granular sludge under mild aqueous conditions.
Keywords: Anaerobic granular sludge; CO2 utilization; Biogas upgrading; Hydrogenotrophic methanogens; Magnesium ribbon; Nesquehonite